Gas Chromatography-Mass Spectrometry (GC-MS) and evaluation of antioxidant and antimicrobial activities of essential oil of Campomanesia adamantium (Cambess.) O. Berg (Guavira) - Isabel Duarte Coutinho; Claúdia Andréa Lima Cardoso; Nilva Ré-Poppi; Adriana Mestriner Melo; Maria do Carmo Vieira; Neli Kika Honda; Roberta Gomes Coelho (Universidade de São Paulo, 2009)
The essential oils from Campomanesia adamantium (Cambess.) O. Berg leaves, collected in the reproductive (flowering and fruit-bearing) and vegetative stages, were characterized by GC-MS (Gas Chromatography-Mass Spectrometry). A total of 95 compounds of the essential oils were identified. In the reproductive stage (flowering) the major constituents were monoterpenes (limonene, α-pinene and β-pinene) while during the vegetative stage the major constituents were the sesquiterpenes (bicyclogermacrene and globulol). The essential oil of the reproductive stage shows high antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans, and all show moderate activity against Escherichia coli. The essential oils were also evaluated for their radical-scavenging activity by DPPH. The chemogeographical variations of the oil composition from the four distinct localities studied all contained α-pinene, β-pinene, limonene, linalool, β-caryophyllene, germacrene D and bicyclogermacrene, however the samples from Jardim city contained neither limonene nor linalool. Os óleos essenciais obtidos das folhas de Campomanesia adamantium foram caracterizados através da combinação de CG-EM e índice de retenção, sendo identificado um total de 95 compostos. Na floração as substâncias majoritárias foram monoterpenos (limoneno, α-pineno e β-pineno) e durante o estágio vegetativo as substâncias majoritárias foram sesquiterpenos (biciclogermacreno e globulol). Os óleos essenciais obtidos da floração e frutificação mostraram alta atividade contra Staphylococcus aureus, Pseudomonas aeruginosa e Candida albicans e moderada contra Escherichia coli em todos os estágios. Foi avaliada a atividade antioxidante dos óleos essenciais usando o método do DPPH. O óleo essencial das 4 cidades mostrou a presença de α-pineno, β-pineno, limoneno, linalol, β-cariofileno, germacreno D e biciclogermacreno, mas a amostra da cidade de Jardim não apresentou limoneno e linalol.